THE USE OF BRAND IMAGE CELEBRITY ENDORSER OF LUWAK WHITE COFFEE TO INCREASE THE PROFIT - Putra Chairy; Adriansyah Adriansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study aims to analyze the influence of celebrity endorser, and brand image of purchase decisions on Luwak White Coffee customers. Purchasing decision is an important thing to do a company to find out how much consumer buying interest in Luwak White Coffee products with the added celebrity endorser. One way to gain competitive advantage in improving purchasing decisions is to form a good brand image in the eyes of consumers and easy to remember always. Data used in this study obtained from a questionnaire conducted in primary and some observation and direct interview with loyal customers Luwak White Coffee in Coffee shop Aceh Medan 2018. The analysis technique used is multiple regression using hypothesis test, that is F test and t test. This research can be concluded based on statistic test that variable celebrity endorser , and brand image together have a positive influence on the purchase decision variable. Based on the t test, celebrity endorser, and brand image positively and significantly affects the purchasing decision. From this research obtained Adila R square (R2) value of 0,75,8 (75,5%) which means that the combination of celebrity endorser and brand image can explain the impact on the purchase decision which increase and the rest is influenced by other variable equal to 24,5 %.